2023
DOI: 10.1021/acs.energyfuels.3c02648
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Carbon Capture and Storage to the Decarbonization of Coal-Fired Power Plants in Selected Asian Countries

Hon Chung Lau

Abstract: About 26% of global CO2 emissions came from coal-fired power plants (CP) in 2021. Furthermore, 72% of this came from Asian countries, especially China and India. Therefore, reducing CO2 emission from CPs is a must if Asian countries were to achieve net-zero CO2 emission by 2050 or soon afterward. In this study, we evaluate the potential contribution of carbon capture and storage (CCS) to decarbonize CPs in selected Asian countries. Our study area consists of the east coast of China, India, Sumatra, West Java … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…This will require compressing the captured CO 2 and transporting it to nearby oil or gas reservoirs, or using saline aquifers for permanent storage. A recent study by Lau showed a potentially large contribution of retrofitting CCS in existing coal-fired power plants in several Asian countries [66]. Which method is preferred will depend on the availability of gas to replace coal and the availability of suitable subsurface storage sites for CO 2 storage.…”
Section: Decarbonization For Coal-dominated Economiesmentioning
confidence: 99%
“…This will require compressing the captured CO 2 and transporting it to nearby oil or gas reservoirs, or using saline aquifers for permanent storage. A recent study by Lau showed a potentially large contribution of retrofitting CCS in existing coal-fired power plants in several Asian countries [66]. Which method is preferred will depend on the availability of gas to replace coal and the availability of suitable subsurface storage sites for CO 2 storage.…”
Section: Decarbonization For Coal-dominated Economiesmentioning
confidence: 99%
“…1,2 The International Energy Agency (IEA) describes 78 pathways to achieve net-zero emissions globally by 2050, which would require the world to capture and store 79 billion tons of carbon dioxide annually. 3,4 As an intermediate link in the CCUS technologies chain, the choice of transportation method plays a crucial role in the deployment of CCUS infrastructure. 5,6 Common transportation methods include tanker truck, tanker train, pipeline and tanker ship.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, Carbon Capture, Utilization and Storage (CCUS) technologies offer a promising pathway for reducing carbon dioxide emissions and combating climate change (Figure ). By capturing, utilizing and storing carbon dioxide emissions, CCUS technologies prevent their release into the atmosphere and minimizes their impact on climate change. , The International Energy Agency (IEA) describes 78 pathways to achieve net-zero emissions globally by 2050, which would require the world to capture and store 79 billion tons of carbon dioxide annually. , As an intermediate link in the CCUS technologies chain, the choice of transportation method plays a crucial role in the deployment of CCUS infrastructure. , Common transportation methods include tanker truck, tanker train, pipeline and tanker ship . Among those methods, pipeline transportation is the primary option for CCUS projects, as depicted in Table .…”
Section: Introductionmentioning
confidence: 99%
“…They include clean coal technologies, 9 carbon capture, utilization and storage (CCUS), 10 renewable energies, 11 nuclear energy, 12 hydrogen, 13−16 and reduced energy demand through adoption of a circular economy. 17 There is also research focused on the decarbonization of various energy consumption sectors such as power, 18−20 transport, 21,22 and industry 23,24 as well as research on the decarbonization of specific countries 20,25−30 and regions. 19,31−33 Besides technologies, economics play an important role in financing the energy transition.…”
Section: Introductionmentioning
confidence: 99%